Improved Routing Protocol in Mobile Ad Hoc Networks Using Fuzzy Logic - Seyed Amin Hosseini Seno; Ali Abdi Seyedkolaei (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
In mobile ad hoc networks, route selection is one of the most important issues that is studied in these networks as a field of research. Many articles trying to provide solutions to choose the best path in which the important parameters such as power consumption, bandwidth and mobility are used. In this article, in order to improve the solutions presented in recent papers parameters such as power remaining, mobility, degree node and available bandwidth are used by taking the factors for each parameter in proportion to its influence in choosing the best path. Finally, we compare the proposed solution with the three protocols IAOMDV-F, AODVFART and FLM-AODV with the help of OPNET simulation program based on network throughput, routing discovery time, the average number of hops per route, network delay.